KONSELING POPULASI KHUSUS;TREATMENT RATIONAL BEHAVIOR TERAPHY PADA SIKAP TEMPRAMEN ANAK TUNALARAS (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2022)
Children are a gift given by God to every family. Children with behavioral, emotional and social disorders need special treatment. Therapy that can reduce temperament in children can use the rational Emotive Behavior Therapy technique, where this technique is a technique that relates emotions, thoughts and behavior. Data collection techniques are through questionnaires, interviews, observation and documentation. Data analysis techniques using a Likert scale with validity tests, reliability tests, and descriptive analysis tests. The results of the research showed that the total pre-test score was 104 from 8 respondents, then after being treated with the rational emotive behavior therapy method, most respondents decreased by 34 points so that the rational emotive behavior therapy method was effective in reducing the temperament of children with special needs in the community of Rancabungur Village, Bogor Regency, because before treatment, the respondent's temperament attitude was very high and after carrying out the treatment, the respondent's temperament attitude decreased. The conclusions are 1) The child's temperament cannot be predicted, 2) The application of rational Emotive Behavior Therapy makes it difficult for the child to concentrate and understand speech, 3) The influence of the application is very large because the mentally retarded need calm. The teacher first provides a contract for Rational Emotive Behavior Therapy techniques and what the child will get. To parents, if they apply these techniques, it must be with a contract agreed upon by the child and parents, and To researchers, to study the effect of applying Rational Emotive Behavior Therapy. .